Stepping Up to New and Better Us - Titik Respati; Herry Garna (Universitas Islam Bandung, 2018)
This is another milestone for our Journal, Global Medical and Health Communication (GMHC). Starting from this volume in August 2018, GMHC will only publish in English. This move is following our mission to be involved in the global arena. The best approach is by publishing in one of United Nation Language official and working languages, and we choose English.